Derivation and Mapping of Critical Loads for Nitrogen and Trends in Their Exceedance in Germany - Hans-Dieter Nagel; Heinz-Detlef Gregor (The Scientific World Journal)
The term “critical load” means a quantitative estimate of an exposure to one or more pollutants below which significant harmful effects on specified sensitive elements of the environment do not occur, according to present knowledge. In the case of nitrogen, both oxidised and reduced compounds contribute to the total deposition of acidity, which exceeds critical loads in many forest ecosystems. These also cause negative effects through eutrophication. Critical loads of nitrogen were derived for forest soils (deciduous and coniferous forest), natural grassland, acid fens, heathland, and mesotrophic peat bogs. In Germany, a decrease in sulphur emissions over the past 15 years resulted in a reduced exceedance of critical loads for acid deposition. In the same period it was noted that reduction in the emissions of nitrogen oxides and ammonia remained insignificant. Therefore, emissions of nitrogen compounds have become relatively more important and will continue to threaten ecosystem function and stability. The risk of environmental damage remains at an unacceptable level. The German maps show the degree to which the critical loads are exceeded, and they present current developments and an expected future trend. Results indicate that recovery from pollutant stress occurs only gradually.